DEVELOPING CREATIVE THINKING IN MANAGING DIGITAL LEARNING - Khandokmai, Saowanee; Khandokmai, Rayong; Sirikanna, Jarmon; Phewngam, Sawitree (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to This research article aims to create guidelines for developing creative thinking skills in managing digital learning and To study the creative thinking skill teaching model of learners in digital learning management. The scope of the research was Mathayomsuksa 6 students of the Demonstration School of Suan Sunandha Rajabhat University in the first semester of the academic year 2022. The target group of 30 students. The research tools were: 1. Instructional plans in physical education subjects 2. Activity performance assessment forms by experimenting with the study plan with Mathayomsuksa 6 students in the physical education subject, the first semester of the academic year 2022, The result shows that 1) A study of problems in teaching and learning to develop creative thinking skills of each subject group. It was found that there were a variety of activities such as mind mapping, poster design. Atomic model design in science subjects, etc. But the process of conducting activities is similar with clear steps. 2) According to the learning management process using the creative learning theory with wisdom (Constructionism) results are Learners are happier with their studies. Learners work more systematically. Learners can create projects that meet their objectives because of work-based learning that requires trying to think and find solutions. and setting up a working system with appropriate steps Make it easier for students to be creative. learners assert themselves more rationally Have good leadership and follower skills Including having the courage to express opinions Be a good speaker and listener.